The expression of COX-2 in VEGF-treated endothelial cells is mediated through protein tyrosine kinase - Pravit Akarasereenont; Kitirat Techatraisak; Athiwat Thaworn; Sirikul Chotewuttakorn (Hindawi Limited, 2002)
Cyclooxygenase (COX), existing as the COX-1 and COX-2 isoforms, converts arachidonic acid to prostaglandin H2, which is then further metabolized to various prostaglandins. Vascular endothelial growth factor (VEGF) has been shown to play important roles in inflammation and is upregulated by the prostaglandin E series through COX-2 in several cell types. Here, we have investigated the effects of VEGF on the COX isoform expressed in human umbilical vein endothelial cells (HUVEC). The signalling mechanism of the COX isoform expressed in endothelial cells activated with VEGF will be also investigated using the tyrosine kinase inhibitor, genistein, and protein kinase C inhibitor, staurosporine. The activity of COX2 was assessed by measuring the production of 6-keto-prostaglandin F1α in the presence of exogenous arachidonic acids (10 μM, 10 min) by enzyme immunoassay. The expression of COX isoform protein was detected by immunoblot using specific antibodies. Untreated HUVEC contained no COX-2 protein. In HUVEC treated with VEGF (0.01-50 ng/ml), COX-2 protein, but not COX-1, and COX activity were increased in a dose-dependent manner. Interestingly, the increased COX-2 protein and activity in response to VEGF (10 ng/ml) was inhibited by the tyrosine kinase inhibitor, genistein (0.05-5 μg/ml), but not by the protein kinase C inhibitor, staurosporine (0.1-10 ng/ml). Thus, the induction of COX-2 by VEGF in endothelial cells was mediated through protein tyrosine kinase, and the uses of specific COX-2 inhibitors in these conditions, in which VEGF was involved, might have a role.